Decreased Severity of Acute Hepatopancreatic Necrosis Disease in White Shrimp (Litopenaeus vannamei) by Mixed Culture of Bacillus subtilis, Bacillus licheniformis and Bacillus megaterium - Saowapha Surawut; Kunyarut Suntara; Winyou Puckdee; Chutapa Kunsook; Pornpimon Kanjanavas; Anchalee Kompatiparn; Prachuab Leeruksakiat (Tropical Life Sciences Research, 2023)
The objective of this study was to investigate the mixed culture of Bacillus subtilis, B. licheniformis and B. megaterium to control acute hepatopancreatic necrosis disease (AHPND) or EMS (Early Mortality Syndrome) in white shrimp Litopenaeus vannamei as a model. The infected shrimps with Vibrio parahaemolyticus AHPND strain were divided into tanks and different feeding of either B. subtilis, B. licheniformis, B. megaterium or all Bacillus strains. The infected shrimps that were fed with a mixed culture of Bacillus showed significantly highest survival rate and revealed lower percent detection of V. parahaemolyticus AHPND strain by Polymerase Chain Reaction (PCR) (57.14%) with a small amount of viability count in their hepatopancreas. In contrast, the infected shrimps that were fed with each of B. subtilis, B. licheniformis or B. megaterium, revealed the spread of V. parahaemolyticus AHPND strain in all tissue by PCR detection (86.67%–100%) with a large amount of viability count (3.53 – 4.24 × 103 CFU/g). This study indicated that the mixed culture of Bacillus subtilis, B. licheniformis and B. megaterium could control the dissemination of V. parahaemolyticus in shrimps, especially in hepatopancreatic that is the target tissue of AHPND in white shrimp (L. vannamei). The result of this study revealed the efficiency and mechanism of the mixed culture of B. subtilis, B. licheniformis and B. megaterium to control the virulence of AHPND and support the application of this mixed culture in aquaculture of shrimp farms to avoid chemical and antibiotic treatment by using it as a biological control.